Wandering spleen as a cause of sinistral portal hypertension - da Silva, Rodrigo Piltcher; Costa, Vicente Lobato; Losekann, Caroline; Wendt, Luiz Roberto Rigo; Trindade, Eduardo Neubarth (Clinical and Biomedical Research, 2021)
Wandering spleen (WS) is a rare entity characterized by laxity of peritoneal ligaments that hold the spleen stationary. It is most commonly diagnosed in children and young women. Clinical presentation ranges from asymptomatic to acute abdomen. A 19-yearold woman came to the emergency department with history of progressive abdominal pain. She also had previous episodes of hematemesis. A computed tomography scan showed an ectopic spleen with a “whirlpool sign.” Laparotomy and splenectomy were performed. WS is characterized by a long vascular pedicle and laxity of peritoneal attachments of the spleen. The etiology is usually congenital. Splenopexy is the main treatment; however, splenectomy is indicated when splenic infarction is present. Despite being rare, this condition may be considered in some cases of abdominal pain. An earlier diagnosis would have allowed us to perform a splenopexy, thus reducing morbidity.